Resveratrol protects human bronchial epithelial cells against nickel‐induced toxicity via suppressing p38 MAPK, NF‐κB signaling, and NLRP3 inflammasome activation. Issue 5 (13th January 2020) - Cao, Xiangyu; Tian, Siqi; Fu, Mingyang; Li, Yanmei; Sun, Yueling; Liu, Jianli; Liu, Yue
Abstract: Nickel is a common environmental pollutant that can impair the lung, but the underlying mechanisms have not yet been fully elucidated. Furthermore, natural products are generally used to inhibit cell damage induced by heavy metal. Resveratrol possesses wide biological activities, including anti‐inflammation and antioxidative stress. This study was conducted to explore the toxicity of nickel on human bronchial epithelial (BEAS‐2B) cells and evaluate the protective effect of resveratrol. The results showed that nickel could induce cell apoptosis, increase oxidative stress, and promote the expression of pro‐inflammatory cytokines, including tumor necrosis factor‐α, interleukin (IL)‐1β, IL‐6, IL‐8, C‐reaction protein. Western blot analysis showed that nickel activated p38 mitogen‐activated protein kinase (MAPK), nuclear factor‐kappa B, and nucleotide‐binding oligomerization domain‐like receptor pyrin‐domain‐containing protein 3 pathways, while resveratrol could reverse these effects. Our results suggested that resveratrol could protect BEAS‐2B cells from nickel‐induced cytotoxicity. Therefore, resveratrol is a potential chemopreventive agent against nickel‐induced lung disease. Abstract : Nickel‐induced cell apoptosis, increased oxidative stress, promoted the expression of pro‐inflammatory cytokines, and activated p38 MAPK, nuclear factor‐kappa B, and nucleotide‐binding oligomerization domain‐like receptor pyrin‐domain‐containing protein 3 pathways. While resveratrol could reverse these effects, by which resveratrol protected BEAS‐2B cells from nickel toxicity.